PSV-40 Effects of regrouping and administrations of meloxicam and chromium on plasma cortisol concentrations and behaviors in dairy calves - Jung, Da Jin Sol (J Anim Sci, 2020)
This study investigated effects of regrouping and oral meloxicam and chromium administration on growth performance, blood cortisol concentrations, and behaviors in dairy calves. Fifty Holstein calves (average age 196 ± 24.7 days, average body weight 198kg ± 32.7 kg) were equally divided into five groups: no regrouping with lactose monohydrate administration (NL), regrouping with lactose monohydrate administration (GL), regrouping with Cr administration (GC), regrouping with meloxicam administration (GM), and regrouping with both meloxicam and Cr administration (GMC). Blood was collected before regrouping and at 3h, 9h, 24h, 1w, and 2w after regrouping. Behaviors have been monitored from d1 to d7. Regrouping did not affect average daily gain (ADG), and the administrations of both meloxicam and chromium increased (P < 0.02) ADG compared to NL group during 2 weeks. Regrouping increased (P < 0.05) plasma cortisol concentrations in GL group, and both meloxicam and chromium and its combination treatments decreased cortisol concentrations compared to GL group at 24h, but not at other times. Regrouping increased (P < 0.05) fight, duration of eating time, head bunt, drinking time, and standing time behaviors in GL group at d1, d2, d2, d3, and d4 respectively. Regrouping also increased (P < 0.05) displacement at eating place in GL group from d3 to d6, but this effect was not significant (P < 0.05) at d7. In conclusion, regrouping caused elevation of plasma cortisol concentrations and abnormal behaviors. Meloxicam, chromium, and/or its combined administrations improved growth performance and reduced circulating cortisol concentrations in regrouped dairy calves, suggesting a feasible strategy to alleviate regrouping stress.